1995
DOI: 10.1007/bf01553520
|View full text |Cite
|
Sign up to set email alerts
|

Continuous passive motion in rehabilitation after anterior cruciate ligament reconstruction

Abstract: In a prospective, randomized study, 34 patients (25 male, 9 female; mean age 27 +/- 8 years) with unilateral anterior cruciate ligament ruptures and arthroscopic reconstruction with patellar tendon grafts were allocated at random to either early active motion only (AM; n = 17) or active motion in combination with continuous passive motion (CPM; n = 17). Range of motion was measured with a goniometer and joint swelling with a tape measure, preoperatively and at 6 weeks postoperatively. Neither associated injuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 12 publications
(14 reference statements)
1
33
0
3
Order By: Relevance
“…58 Multiple studies have shown that the use of a CPM does not affect range of motion or anterior laxity after ACL reconstruction. 57,[59][60][61] Given the cost associated with CPM and the lack of effect on overall functional outcomes, it is hard to justify their use as purely an adjunct to pain control without definitive level 1 supportive evidence. 62…”
Section: Continuous Passive Motion Devicesmentioning
confidence: 99%
“…58 Multiple studies have shown that the use of a CPM does not affect range of motion or anterior laxity after ACL reconstruction. 57,[59][60][61] Given the cost associated with CPM and the lack of effect on overall functional outcomes, it is hard to justify their use as purely an adjunct to pain control without definitive level 1 supportive evidence. 62…”
Section: Continuous Passive Motion Devicesmentioning
confidence: 99%
“…Methods of the analysis and inclusion criteria were specified in advance, documented in a protocol and published on the Prospero international prospective register of systematic reviews, registration number CRD42014015077. The systematic literature search, the analysis and synthesis were performed according to the PRISMA statement [13].…”
Section: Protocol and Registrationmentioning
confidence: 99%
“…Obwohl die Orthesenverwendung in unserer Umfrage bei 82,8 % der Befragten üblich ist und in den aktuellen DGOU-Nachbehandlungsempfehlungen bis 6 Wochen postoperativ empfohlen wird, gibt es kaum Evidenz, die einen Ortheseneinsatz unterstützt. In einer Arbeit von Giotis [11]. Der nicht nachgewiesene Benefit durch die CPM-Schiene wurde auch in einer Literaturzusammenfassung im Rahmen der MOON-Leitlinien unterstrichen [41].…”
Section: Ergebnisseunclassified